Total Physical Response in Vocabulary Learning: A Qualitative Study in Fourth Grade Students - Salma Zakiyah; Leny Saili Rahmah; Hamdan Hidayat (Universitas Islam Negeri Palopo, 2026)
This study addresses low students’ engagements and limited vocabulary retention under traditional instruction at a public primary school in Bandung Regency. It aims to examine the qualitative implementation of the Total Physical Response (TPR) method and analyze its role in fostering student engagement. Unlike previous studies that predominantly measure TPR’s quantitative effectiveness, this study offers a novel contribution by exploring the deep qualitative nuances and lived experiences of young learners during the physicalization of words. Using a descriptive qualitative design, data were collected through observations, semi-structured interviews, and documentation, then analyzed using the framework (Miles et al., 2014). The results revealed that TPR successfully trnasformed the passive classroom into an interactive environment, enhancing student immersion and behavioral engagement. Qualitative insights described a substantial improvement in English vocabulary retention, while also uncovering a nuanced spectrum of individual learning preferences, including students who still favored text-based learning. This study concludes that while TPR effectively breaks traditional passivity, primary school educators should practically integrate multi-sensory activities with diverse instructional methods to effectively accommodate distinct cognitive learning styles in daily vocabulary teaching.